2017
DOI: 10.1080/24750263.2017.1315184
|View full text |Cite
|
Sign up to set email alerts
|

New data on fish diet and bone digestion of the Eurasian otter (Lutra lutra) (Mammalia: Mustelidae) in central France

Abstract: Fish remains are abundant and easily recognizable in many archaeological sites. The origin of such assemblages is generally poorly known. The ability to create small fish bone accumulations is restricted to a small number of predators (including raptors, carnivores and humans). In order to recognize the agents responsible for these concentrations in archaeological sites, we have investigated the taphonomy of the fish remains from otter spraints to determine the potential role of the Eurasian otter, Lutra lutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Five categories of digestion were distinguished: null (0); light (1); moderate (2); heavy (3); and extreme (4-5). For fish bones, the digestion degrees have been illustrated in Guillaud et al (2017). The action of gastric juices results in a smooth and polished surface (Andrews 1990); and although the prolonged transportation of bones in water can also produce this result, only digestion could have caused these effects in our study.…”
Section: Digestionmentioning
confidence: 77%
See 1 more Smart Citation
“…Five categories of digestion were distinguished: null (0); light (1); moderate (2); heavy (3); and extreme (4-5). For fish bones, the digestion degrees have been illustrated in Guillaud et al (2017). The action of gastric juices results in a smooth and polished surface (Andrews 1990); and although the prolonged transportation of bones in water can also produce this result, only digestion could have caused these effects in our study.…”
Section: Digestionmentioning
confidence: 77%
“…Prey sizes were estimated by direct comparison with specimens from the osteological reference collection of the MNHN. Following the methodology used in a previous study (Guillaud et al 2017), surface modification was classified following Nicholson (1991). The percentage of visible surface was adapted from Villa & Mahieu (1991).…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous papers on actualistic studies for the northern hemisphere; thus, there is currently a fairly broad picture of the modifications that different predators produce on the bones of small mammals (e.g., Andrews, 1990; Fernández-Jalvo and Andrews, 1992;Laudet and Selva, 2005;Lloveras et al, 2008;Esteban-Nadal et al, 2010;Denys, 2011;Souttou et al, 2012;Fernández-Jalvo et al, 2016;Campmas et al, 2018;Denys et al, 2018;Royer et al, 2019). Samples of small fish, amphibians, reptiles and birds were only occasionally evaluated; in those cases, an alternative methodology was used to better fit the morphology of the bones of these microvertebrates (Bochenski et al, 1993(Bochenski et al, , 2009Bochenski and Tomek, 1994;Pinto Llona and Andrews, 1999;Castillo et al, 2001;Bochenski and Tornberg, 2003;Bochenski, 2005;Broughton et al, 2006;Bailon, 2011;Russ and Jones, 2011;Guillaud et al, 2017). Andrews (1990) and Fernández-Jalvo and Andrews (1992) suggested that the most relevant criterion to distinguish the effects produced during predation on small mammal bones is the evaluation of the modifications of their surface caused by the digestive acids of the predator.…”
Section: Current Status Of the Taphonomy Of Small Mammalsmentioning
confidence: 99%
“…The otters’ feces (spraints) are useful for their diet analyses [3, 4, 6] and individual identification [7, 8]. Morphological observation of undigested food remains, such as bones, shells, and hair, in spraints provides information regarding the otters’ diets [3, 6]. Previous studies reported fishes as the otters’ main preys followed by amphibians, crabs, birds, and insects [3, 4].…”
Section: Introductionmentioning
confidence: 99%